Aktuelle Entwicklungen der IuK-Technologien — Konsequenzen für räumliche Entwicklung und Raumplanung - Langhagen-Rohrbach, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
Innovation is leading to several new technologies in ICT every year — while mobile phones and the Internet where the leading innovation in the ICT-sector of the 1990s, now the integration of those networks is more important. Due to increasing bandwidths and new wireless technologies more services can be provided by actual data networks. This essay is showing latest developments in ICT and discusses their importance for spatial planning because of their power to influence or even change spatial stuctures.